Adiamento de recompensa e a autorregulação emocional em crianças com transtorno de déficit de atenção/hiperatividade - Utsumi, Daniel Augusto [UNIFESP] (2015)
Current research in neuropsychology show the importance of investigating the hot executive processes in Attention-Deficit/Hyperactivity Disorder (ADHD) as the reward delay and emotional self-regulation. Temporal Discounting (TD) paradigm has been used for the assessment of reward delay and impulsivity in ADHD and reflects the trend of devaluation of a given reward as the time of delivery is delayed. This study aimed to analyse the performance of children with and without ADHD into three types of TD tasks, correlating the results with emotional self-regulation measures of Behavior Rating Inventory of Executive Functions (BRIEF) and Child Behavior Checklist (CBCL) scales. The study included 49 children aged 8-12 years, divided into two groups: 25 children with ADHD and 24 controls. For the evaluation of TD were developed three types of tasks: 1) hypothetical - in which the reward was not delivered and the time intervals have not been expected, 2) hypothetical with temporal expectation - in which the reward was not delivered, but the time intervals could be expected and 3) real - in which the reward was delivered and the time intervals could be expected. We used material reward (toys), one of which was given to the participant at the end of the real task in view of the ecological analysis of reinforcement aspects on the choice of the participants. Difference was observed between the groups in the hypothetical with temporal expectation task, in which the ADHD group showed a higher rate of depreciation of the favorite toy. A strong correlation between levels of emotional self-regulation proposed by the BRIEF and CBCL scales was observed. The hypothetical with temporal expectation task correlated significantly and negatively with behavioral regulation index and inhibition scale of BRIEF, suggesting associations between impulsivity and low emotional self-regulation. However, no TD task correlated with the CBCL. It was concluded that tasks involving toys can be used to evaluate the TD construct, especially the hypothetical with temporal expectation task, which was sensitive to evaluate the reward delay concept. It can also be used in future research for the differenciation of clinical groups and as a complementary tool for the assessment of emotional self-regulation.